From Togetherness to Individualism: The Evolving Meaning of Ngabuburit Among Teenagers - Jazilah, Jazilah; Ririh Megah Safitri, Ririh Megah (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2024)
The tradition of ngabuburit among teenagers has experienced significant transformation due to advancements in technology and the influence of popular culture. This study employs qualitative methods to (1) explore how teenagers interpret the ngabuburit tradition in the digital era, (2) identify the factors driving changes in its meaning, and (3) analyze the social impacts of these changes on teenagers' lives. Findings reveal that ngabuburit activities have shifted toward individualistic and consumerist tendencies, such as spending time in trendy locations and showcasing moments on social media, rather than fostering spirituality and togetherness. This study highlights the deep influence of digitalization on local traditions and underscores the challenges of preserving traditional values in an evolving cultural landscape.